PENGEMBANGAN PENILAIAN AUTENTIK - Moh Maulidin Alif Utama (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
The purpose of education itself is creating a generation that is not only clever in terms of knowledge, but a generation that has a spiritual attitude, adopting noble and have a beneficial skill for himself, the community, the nation and the State. The purpose of education can be said to achieve optimal results then the need for an assessment of the learning process of learners. The assessment is a general term that includes all the usual methods used to assess the performance of students in learning. In curriculum 2013 of his judgement is one of the cornerstones of authentic assessment, teachers assess competency and learning outcomes based on with what has been achieved by learners in their learning.Authentic assessment is an assessment that is conducted to assess the real teachers who have done good learners process as well as results by using a variety of techniques and instruments of valid assessment so that it can be proved that competence set out really has mastered by learners.  authentic assessment include the competencies, knowledge, attitudes and skills. authentic assessment include the competencies, knowledge, attitudes and skills.The goal of authentic Assessment itself, among others, (1) assess the ability of the individual through a specific task, (2) determine the needs of learning, (3) assist and encourage students. the implementation of the Authentic assessment using many of the techniques that can be used to assess the competency of attitude (observations, self-assessment, peer reviewed, journal entry teacher and interview), knowledge (oral test, test and assignments), and skills (performance assessment, projects, and portfolio assessment). as for the format of the assessment of each competency that exists in the assessment of authentic can be developed by teachers.